Malaria Cases in Jayapura District, Mimika District, and Jayapura City, Papua 2023 - Nisa Fauziah; Leonard H Jososudarmo; Budi Sujatmiko; Naufal Fakhri Nugraha; Jontari Hutagalung (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Papua has been known as the highest number of cases of malaria in indonesia; however, there has been a little shortage of studies on the distribution of the malarian cases in the area. Lack of studies on distribution and proportion of malaria cases in Papua region can affect the surveilance of malaria, therefore this study is carried out. This is a descriptive study with explorative research design, observation approach on secondary data, and analysis with the help of Geographic Information System (GIS). Population of the study is all malaria patients recorded in 8 health facilities in Mimika District, Jayapura District, Jayapura City between March and May 2023. The results shown total malaria patients is 128 people with various proportion of demographics aspects including age, sex, ethnicity, duration of stay, health care facilities. Propotion of malarian cases by the Plasmodium species, health care facilities distribution, and months recorded was also obtain with the highest number of malaria cases is caused by Plasmodium falciparum (44,53%), found in Mimika District and according in healthcare facilities is Primary Health Care (PHC) Mimika, and found in March. It is also found there is an increase of cases from March to May in Mimika District. The distribution of cases vary can be caused by difference of geographical condition, sanitary condition of the area, area’s climate, proportion of ethinic, people’s activities, and risk factors.